Managing organizational communications in the multicultural environment - Valeriya Volkova (Менеджмент та підприємництво: тренди розвитку, 2019)
The study is aimed at analyzing the issues of managing organizational communications in the multicultural business context and revealing the main difficulties in providing effective cross-cultural communications at enterprises in terms of organization and staff development. Methodology: the research can be defined as executing an investigation to acquire additional knowledge on the issue of managing organizational communications in the multicultural environment. In the study, a combination of critical analysis, synthesis and comparison was applied as the basic research principles. The subject matter of this paper is organizational communications in multi-national business environment. The relevance of the research is determined by the need to increase the effectiveness of cross-cultural organizational communications at domestic enterprises in order to provide their development and successful functioning in the multicultural environment. Currently, cross-cultural business communications are given much importance, since they require more thorough planning and strict control, compared to internal communications. Under such conditions, the success of interaction depends on reaching an agreement on the rules and methods of communication acceptable to representatives of various cultures. The most important issue in the study of cross-cultural professional communication is research of its effectiveness dependence on the level of intercultural competence of communicants. Intercultural competence, including the knowledge and skills, refers to most problematic aspects of managing communications of companies operating in the multicultural environment. Adaptation of management to the conditions of the environment can result not only in gaining congruence in the various cultures the organization operate in, but also in increasing the communications effectiveness to the extent ensuring performance efficiency at the cross-cultural level. In today’s multicultural business environment companies frequently encounter cultural differences, which can impede effective performance and successful achievement of organizational goals. Increased globalization of business processes has set the task not only to correctly identify differences in the national cultures, but also to adequately use them to overcome the intercultural difficulties while establishing and developing relations with foreign partners. Optimizing cross-cultural professional communications and increasing the intercultural competence of personnel becomes essential to the organization’s performance effectiveness. Ensuring effectiveness of the organization’s performance in a multicultural environment is closely related to exploring the ways of increasing the competitiveness of Ukrainian enterprises globally. The present research contributes to this area by offering valuable insights into cross-cultural communications in organizations with a multicultural environment and the ways of optimizing communications management.